Muslim/christian politics of religion in Nigeria: the shariah application and the religious foundations of global muslim engagement with modernity (2014)
Contrary to the traditional modernist theories that development and progress can can be achieved through the western secular modernizing project, many Islamic societies are rejecting modernisms and the modernization project to borrow (arnason 2003), “as an organic globalization process” but not “as a globalizing civilization in the plural.” This paper differentiates between Islamic modernity and western modernity, and within this theoretical framework, demonstrates how muslins in Nigeria differ from Christians on the shariah application and the relation between religion and state. It also examines how this engagement reflects global muslins commitment to progress and development without submitting to a uniform, integral and singular modernist theory. Then paper, while comparing this engagement with modernity in both Nigeria and Malaysia, submits that the politics of religion playing out in Nigeria where many Muslim and Christians denigrate and resent each other in the “name of God” amidst their rivalry for the control of the country’s resource could be bought to an end if Nigeria adopts the Malaysians modern model of modernity which has fused religion (Islam) and development , while rejecting some aspect of western modern modernity like western democracy, comprehensive secularism liberalism and Greek rationality.